Design of Water Heating By Utilizing Waste Heat of Air Conditioner - Hasan Basri; Ery Diniardi; Anwar Ilmar Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2021)
This plan aims to minimize wasted energy in the air freshener system and utilize the wasted energy to heat water. Here using a split type air conditioner system which is commonly used. The author slightly modified the air conditioning system which previously used an air conditioning condenser, here the author added a condenser with a water cooler that functions as a condenser and at the same time as a water heater. The energy used to heat the water is obtained from the heat released by the refrigerant so as to minimize the energy wasted when only using an air conditioning condenser. But the air conditioning condenser is still used in this system, because when hot water is not needed, the water in the heater does not flow and of course cannot take heat from the refrigerant. In this condition the air conditioning condenser can work to help the process of releasing heat from the refrigerant. This tool can heat water up to 43oC with a flow rate of 1 liter per 9 seconds which can be used at home, SOHO, office for bathing, washing face, washing hands, etc.